The feasibility of wind and solar energy application for oil and gas offshore platform - Tiong, Y.; Zahari, M.; Wong, S.; Dol, Sharul sham (2015)
Renewable energy is an energy which is freely available in nature such as winds and solar energy. It plays a critical role in greening the energy sector as these sources of energy produce little or no pollution to environment. This paper will focus on capability of renewable energy (wind and solar) in generating power for offshore application. Data of wind speeds and solar irradiation that are available around SHELL Sabah Water Platform for every 10 minutes, 24 hours a day, for a period of one year are provided by SHELL Sarawak Sdn. Bhd. The suitable wind turbine and photovoltaic panel that are able to give a high output and higher reliability during operation period are selected by using the tabulated data. The highest power output generated using single wind energy application is equal to 492 kW while for solar energy application is equal to 20 kW. Using the calculated data, the feasibility of renewable energy is then determined based on the platform energy demand.